Endoscopically Assisted Percutaneous Achilles Tendon Repair: A Biomechanical and Clinical Pilot. Issue 4 (16th October 2019) - Carpenter, Daniel; Dederer, Katherine; Weinhold, Paul; Tennant, Joshua N
Category: Arthroscopy, Sports, Trauma Introduction/Purpose: Achilles tendon rupture treatment includes non-operative, minimally invasive, and open repair techniques. Clinical outcomes of a cohort of patients undergoing a percutaneous endoscopically assisted technique (PEAT) were compared to those of a cohort of non-operatively treated Achilles tendon ruptures. The PEAT repair technique described is a novel method which avoids a proximal lateral incision. We sought to determine clinical outcomes from a cohort undergoing this procedure as well as its basic biomechanical properties. Methods: Clinical: With IRB approval a cohort of operatively treated patients was assessed with the following PROs: Return to sport, VAS pain score, Satisfaction Likert, patient reported complications, single heel lift, patient reported medical & smoking history, ATRS (Achilles Tendon Rupture Score). Chart review of diagnostic modality, injury mechanism, time to surgery, tourniquet times, and surgeon reported complications were also collected. Biomechanical: 6 pairs (12) of age and sex matched fresh frozen lower extremity specimens (mid tibia to toes) with average age 71.5 (48-89) (8 F specimens, 4 M specimens) underwent either open (Kessler) repair or percutaneous repair. Specimens were cycled 10N-43 N for 100 cycles, and 20N-86 N for 200 cycles, measuring displacement and ultimate load to failure. Results: Clinical: 30 patients operatively treated with the PEAT procedure, 22 contacted by phone. Avg. follow up 2.5 years (1.2- 3.8); Avg ATRS 94.1 (81-100, SD 4.8); "very satisfied" 19/20; Avg VAS 0.3. We had a re-rupture rate of 3.33% (1/30). Biomechanical data: At 10-43 N for 100 cycles, all 12 specimens survived for duration of testing with biomechanical equivalence. At 20-86 N for 200 cycles, percutaneous repairs with greater cyclical displacement (1.7 cm vs 1.0 cm); 1/6 percutaneous with early failure; 11/12 specimens survived. Conclusion: The PEAT repair of Achilles tendon rupture showed excellent clinical outcomes with low complications and with biomechanical testing suggesting equivalent strength at low loads.